Baroreflex activation therapy in patients with end-stage renal failure. Issue 11 (November 2015) - Beige, Joachim; Koziolek, Michael J.; Hennig, Gert; Hamza, Amir; Wendt, Ralph; Müller, Gerhard A.; Wallbach, Manuel
<x xml:space="preserve">Abstract</x> Background: Resistant arterial hypertension and chronic kidney disease (CKD) are interlinked via sympathetic overactivity. Baroreflex activation therapy (BAT) is a well tolerated therapy, which has been shown to reduce BP in patients with resistant hypertension. The effects of BAT in patients with resistant hypertension and end stage renal disease have not been reported. Method and results: We retrospectively analyzed procedural effectiveness and safety in seven CKD stage 5D patients with resistant hypertension who underwent BAT. One year after activation, office SBP decreased significantly from 194 ± 28 to 137 ± 16 mmHg (P < 0.01). Ambulatory SBP showed a trend to be decreased from 167 ± 30 to 137 ± 24 mmHg (P = 0.17), whereas the median number of prescribed antihypertensive classes decreased from 5 (4–9) to 3 (1–4) (P = 0.01). Intraoperative drop of SBP was −34.3 ± 34.4 mmHg (P = 0.04). With respect to adverse events there were minor side-effects (mainly paresthesia and dysphagia) reported in our patients, which occurred according to treatment intensity and modality. Conclusion: BAT is an effective and well tolerated intervention to reduce BP in patients suffering from end-stage renal disease and resistant hypertension. Therefore, BAT might contribute to a reduction of cardiovascular events in those high-risk patients.